COMPUTERIZED POLYGRAPHIC SYSTEMS: ANALYSIS OF EFFICIENCY AND PRACTICAL APPLICATION - ZENKIN, MYKOLA; KOKHANOVSKYI, VASYL; IVANKO, ANDRII (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The academic paper examines the importance of integrating digital technologies in the printing industry in light of global development trends and growing market demands. The relevance of the research is due to the rapid implementation of digital technologies in all spheres of activity, which inevitably affects the printing industry, requiring a detailed analysis of the effectiveness and possibilities of using computerized systems. The development of digital printing opens up new horizons for increasing the productivity and quality of printed products, offering greater opportunities for personalization, quick changes of layouts and savings on medium and small runs. The main part of the academic paper reveals a comparison between traditional and digital printing technologies, highlighting the advantages of the latter in terms of time, cost and quality. Separate consideration is given to the potential of digital printing on textiles, laser printing, and Computer-to-Plate (CTP) technology, all of which greatly improve production processes and lessen environmental effects. The research also focuses on 3D printing, which opens new perspectives for the printing industry, offering high quality, speed and cost-effectiveness of production. The practical significance of the study is to provide specific recommendations and directions for using computerized technologies in the printing industry aimed at increasing the productivity, quality and economic efficiency of the production of printed products. The research shows how the use of computerized systems can simplify production processes, reduce time for production preparation and reduce printing costs, especially when producing medium and small runs. Automation makes it possible to achieve high accuracy and print quality, ensuring better color reproduction, image clarity and uniformity of each print. The conclusions emphasize that the automation and digitization of the printing industry not only increase the efficiency of production processes but also open up new opportunities for the development of the industry in the context of globalization and growing competition. The authors recommend further studies in the field of optimizing the use of digital technologies, which will allow for higher quality of printed products, lower costs and more efficient use of resources, which is critical for the sustainable development of the printing industry.
Keywords: industrial engineering; computerized printing systems; printing equipment; CTP - printing; 3D printing; stereolithography; layer-by-layer fusing